Pemanfaatan Media Teks Multimodal dalam Pembelajaran Cerita Rakyat pada Siswa Kelas V SD Negeri 88 Pinrang - Putri Wulandari; Mayong Mayong; Baharman Baharman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the use of multimodal text media in folklore learning in grade V students of SD Negeri 88 Pinrang, including the application of media, student responses, and obstacles faced by teachers and students in learning. This study uses a type of qualitative method with a qualitative descriptive design. Data collection is carried out through observation or observation in the learning process, using media use checklists, interviews, and using student response questionnaires. The data analysis techniques used are data reduction, data presentation, and conclusion drawn. The results show that the use of multimodal text media, such as images, sounds, and videos, can attract students' attention, increase motivation, and help them understand the cultural values contained in folklore. Limited infrastructure, devices, and networks are some of the challenges encountered. However, it is evident that multimodal text media increases students' interest, active participation, and understanding of the lessons. This research is expected to contribute to the development of more innovative and contextual learning methods in elementary schools.